2006
DOI: 10.1002/chem.200500904
|View full text |Cite
|
Sign up to set email alerts
|

Unusual High‐Temperature Structural Behaviour in Ferroelectric Bi2WO6

Abstract: The crystal structure of Aurivillius phase ferroelectric Bi2WO6 has been studied in detail as a function of temperature by using high-resolution powder neutron diffraction. In agreement with an earlier study, a transition from space group P2(1)ab to B2cb occurs at about 660 degrees C. This transition corresponds to the loss of one octahedral tilt mode within the perovskite-like WO4 layer of the structure. A second, reconstructive, phase transition occurs around 960 degrees C, corresponding to the ferroelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
138
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 17 publications
12
138
0
Order By: Relevance
“…Experimental studies [13] showed that Bi 2 WO 6 is polar at ambient temperature with orthorhombic P 2 1 ab (No. 29) structure.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies [13] showed that Bi 2 WO 6 is polar at ambient temperature with orthorhombic P 2 1 ab (No. 29) structure.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] The room-temperature structure of Bi 2 WO 6 was refined using the P2 1 ab space group (the nonstandard setting of Pca2 1 was used in order to conform with the convention in Aurivillius phase ferroelectrics of assigning the long axis as c, and the polar axis as a), and it exhibits a second-order phase transition at 660 • C to the B2cb ferroelectric phase (nonstandard setting of Aba2) and a first-order phase transition at 960 • C to A2/m non-ferroelectric phase. [6] Recent studies showed that the photocatalytic properties of Bi 2 WO 6 depend on morphology and particle size. [10] It was shown for many materials that a change in the particle size may lead to significant structural changes: for instance, stabilization of the high-temperature phase, or even the appearance of new phases not observed for the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [11] synthesized porous Bi 2 WO 6 thin films, which possess high catalytic activity under visible light irradiation. McDowell et al [12] studied the Aurivillius phase ferroelectric Bi 2 WO 6 . Zhao et al [13] reported an electrospinning method to synthesize one-dimensional Bi 2 WO 6 nanofibers with an excellent visible photocatalytic property.…”
Section: Introductionmentioning
confidence: 99%